Edukasi Pola Makan Bergizi melalui Komunikasi Antar Pribadi pada Ibu Hamil di Wilayah Kerja Puskesmas Belimbing - Azrimaidaliza Azrimaidaliza; Annisa Dwi Apriliani; Windi Lisri Silvia Siregar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
The stunting rate in toddlers is still high in West Sumatra Province, including Padang City. These nutritional problems are inseparable from the mother's role in maintaining her health and nutrition before, during, and after pregnancy or childbirth. Nutritious food is recommended to meet the mother's needs and the fetus's growth and development. The activity aims to increase mothers' understanding of the consumption of nutritious food during pregnancy and their ability to apply it in their daily lives. The activity was carried out through nutrition education accompanied by individual counselling from house to house in the work area of the Public Medical Center in Belimbing, Padang City. Leaflets were distributed to pregnant women to help them understand the material presented. A total of 20 pregnant women were involved in this activity and were enthusiastic about it, as can be seen from the questions asked of the educators. The activity resulting in this education effectively increases the mother's knowledge. With personal communication, this problem can be overcome. Thus, mothers with malnutrition will better understand the nutritious food that must be consumed.